2008
DOI: 10.1007/s11099-008-0077-x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf area estimation by simple measurements and evaluation of leaf area prediction models in Cabernet-Sauvignon grapevine leaves

Abstract: For two growing seasons (2005 and 2006), leaves of grapevine cv. Cabernet-Sauvignon were collected at three growth stages (bunch closure, veraison, and ripeness) from 10-year-old vines grafted on 1103 Paulsen and SO4 rootstocks and subjected to three watering regimes in a commercial vineyard in central Greece. Leaf shape parameters (leaf area − LA, perimeter − Per, maximum midvein length − L, maximum width − W, and average radial − AR) were determined using an image analysis system. Leaf morphology was affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 31 publications
7
24
0
2
Order By: Relevance
“…Similar results were obtained by Antunes et al (2008), Tsialtas et al (2008), Mazzini et al (2010), and Padrón et al (2016), when studying respectively coffee, grapevine, citrus, and bell pepper with models presenting high R² by using the product of the leaves length times width. This can be explained due to shape differences in each leaflet, which may vary from more lanceolate to more oval.…”
Section: Resultssupporting
confidence: 80%
“…Similar results were obtained by Antunes et al (2008), Tsialtas et al (2008), Mazzini et al (2010), and Padrón et al (2016), when studying respectively coffee, grapevine, citrus, and bell pepper with models presenting high R² by using the product of the leaves length times width. This can be explained due to shape differences in each leaflet, which may vary from more lanceolate to more oval.…”
Section: Resultssupporting
confidence: 80%
“…ESTStatistics; SB -Shading; PS -Full sun. tanto nas folhas do ambiente sombreado quanto a pleno sol, assegurando coeficientes de determinação (R 2 ) com valores de até 0,9959 (Tabela 2). Os resultados alcançados neste trabalho estão em conformidade com as regressões mais representativas da estimativa da área foliar, as quais envolveram o produto CL (SEDAR; DEMIRSOY, 2006;PEKSEN, 2007;TSIALTAS et al, 2008;SCHMILDT et al, 2014). Não obstante, em outros trabalhos, os melhores resultados ocorreram com a maior largura do limbo foliar TOEBE et al, 2012) ou com o maior comprimento ao longo da nervura principal (POSSE et al, 2009).…”
Section: Resultsunclassified
“…Many non-destructive models have been recommended for estimating individual leaf area from simple measurements for several tree species [4,5,7,[8][9][10][11][12][13][14][15], vegetables [2,[16][17][18], ornamentals [19][20][21] and other important crops [22], but a leaf area estimation model for citrus genotypes has not been found. The reported models have shown that there are close relationships among leaf width, leaf length and leaf area [4].…”
Section: Introductionmentioning
confidence: 99%